Qualitative exploration of patient and healthcare professional perspectives on barriers and facilitators to foot self-care behaviors in diabetes. Issue 6 (14th November 2022) - Hill, Andrew; Ellis, Mairghread; Gillison, Fiona
Abstract : Introduction: Diabetic foot ulcers contribute significantly to morbidity and mortality associated with diabetes, but are preventable with good foot self-care. This study sought to explore the perspectives of patients and healthcare professionals (HCPs) on barriers and/or facilitators to foot self-care behaviors in diabetes and areas of consensus and/or tension between patient and HCP perspectives. Research design and methods: This was a sequential, qualitative study that used a hermeneutic phenomenological approach. Phase I involved nine in-depth, semi-structured patient interviews. Phase II involved seven in-depth semi-structured interviews with HCPs (podiatrists, diabetes nurses, foot health practitioners (FHPs) and general practitioners (GPs)). In phase III, findings from phases I and II were brought back to two patient interview groups (five patients in total) to try and identify any areas of consensus and tension between HCP and patient perspectives. Results: Patient and HCP perspectives had several areas of alignment: concerns over consequences of diabetes complications; the importance of patient education and frustrations around aspects of health service delivery. There were also some notable tensions identified: mixed messaging from HCPs around whose responsibility patient foot health is; and who patients should initially consult following the development of a foot problem. Overall, patients expressed that motivation to undertake good foot self-care behaviors was generated from their lived experiences, and was enhanced when this aligned with the information they received from HCPs. HCPs appeared to attribute lack of patient motivation to lack of knowledge, which was not raised by patients. Conclusions: This study has identified points of misalignment between the views of patients and practitioners that may help to explain why adherence to foot self-care among patients with diabetes is low. Our results suggest that better outcomes may stem from HCPs focusing on supporting autonomous motivation for self-care and enhancing the rationale through referencing patients' own experience rather than focussing on increasing patient knowledge. Renewed focus on consistency of messaging by HCPs around the roles and responsibilities relating to foot health in diabetes, and the benefit of foot-specific training being provided to non-foot specialist HCPs may also help to improve uptake and adherence to foot self-care behaviors in diabetes.